2003
DOI: 10.1021/la020815g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Calcite Dissolution Using Environmentally Benign Polyaspartic Acid:  A Rotating Disk Study

Abstract: The removal of calcium mineral deposits from metal surfaces is of practical interest for a variety of fields (i.e., food, petroleum, and chemical industries). This study investigated the mechanisms of calcite (CaCO3) dissolution using environmentally benign polyaspartic acid (PASP) under controlled hydrodynamic conditions by a rotating disk technique. The specific role of PASP conformation and surface interactions in the dissolution process was further studied using scanning electron microscopy and dynamic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…In paper (Wu & Grant, 2002) it was found that aspartyl residues undergo protonation, deprotonation and complexation in solution. For sodium polyaspartate with a molecular weight of 10 000, 72 repeated units of aspartyl residues can be recognized as 18 independent hypothetical polyaspartic acid molecules (denoted as H 4 ds) for which the pKs of DS are equal to: pK 1 =2.27, pK 2 =3.60, pK 3 =4.09, pK 4 =5.17, At pH 1 about 100 % of DS occurs as H 4 ds, at pH 3 about 70 % occurs as H 3 ds -, at pH 4 about 48 % occurs as H 2 ds 2-, at pH 4,8 about 65 % occurs as Hds 3-and at pH above 7 100% occurs as ds 4- (Burns, et al 2003). The formation of metal complexes with DS can be summarized as:…”
Section: Dsmentioning
confidence: 92%
“…In paper (Wu & Grant, 2002) it was found that aspartyl residues undergo protonation, deprotonation and complexation in solution. For sodium polyaspartate with a molecular weight of 10 000, 72 repeated units of aspartyl residues can be recognized as 18 independent hypothetical polyaspartic acid molecules (denoted as H 4 ds) for which the pKs of DS are equal to: pK 1 =2.27, pK 2 =3.60, pK 3 =4.09, pK 4 =5.17, At pH 1 about 100 % of DS occurs as H 4 ds, at pH 3 about 70 % occurs as H 3 ds -, at pH 4 about 48 % occurs as H 2 ds 2-, at pH 4,8 about 65 % occurs as Hds 3-and at pH above 7 100% occurs as ds 4- (Burns, et al 2003). The formation of metal complexes with DS can be summarized as:…”
Section: Dsmentioning
confidence: 92%
“…This is also shown by the growth of the Raman peak at 1083 cm -1 of 16 O-calcite over time ( Figure 3) and can be explained by the transformation of the initial metastable carbonates into more stable phases over time. [64][65][66][67][68][69][70][71][72][73][74][75][76][77] Figure 3 shows the disappearance over time of a peak at 495cm -1 that can be related to metastable hydrated phases 55 . Earlier, Rodriguez-Blanco et al 70 described the transformation mechanism of ACC to calcite as a two stage process: 1) ACC particles rapidly dehydrate and crystallize forming individual particles of vaterite; 2) the vaterite dissolves and re-precipitates as calcite (Ogino et al 71 also confirmed the latter stage also for aragonite O ratio within the first 24h.…”
Section: -33mentioning
confidence: 99%
“…The promotions of the dissolution rate and step velocity of calcite were observed in acidic organic compounds such as tartaric acid, alginic acid, and polyaspartic acid additive aqueous solution [31][32][33]. These acidic compounds might attack the calcite surface and promote calcite dissolution, although they can block reactive kink sites on calcite surface and inhibit the dissolution process [31].…”
Section: Promotion Effect Of L-asp On the Surface Processesmentioning
confidence: 99%